Utilizing DNA barcoding approach to study the diversity of the blue swimming crab from Tuban District, East Java, Indonesia - MARITA IKA JOESIDAWATI; NINING NURSALIM; NENIK KHOLILAH; EKA MAYA KURNIASIH; NI KADEK DITA CAHYANI; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Joesidawati MI, Nursalim N, Kholilah N, Kurniasih EM, Cahyani NKD, Ambariyanto A. 2023. Utilizing DNA barcoding approach to study the diversity of the blue swimming crab from Tuban District, East Java, Indonesia. Biodiversitas 24: 4731-4737. Blue swimming crabs are one of the economically significant fisheries resources in Indonesia. However, Indonesia's blue swimming crab fisheries still depend on wild catches that lead to a non-target species harvest, especially the cryptic swimming crabs. This study aims to investigate the genetic diversity of blue swimming crab specimens and other cryptic species using a molecular approach (DNA Barcoding). The samples were caught from the waters of Tuban District, East Java, Indonesia, using traditional foldable traps or